2021
DOI: 10.1093/pubmed/fdab376
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outcomes among pregnant and nonpregnant women at reproductive age in Egypt

Abstract: Background To describe demographic, clinical and epidemiological characteristics of pregnant and nonpregnant women with confirmed COVID-19 at reproductive age and determine risk factors of COVID-19 severe outcomes during pregnancy. Methods A retrospective study for females aged 18–49 with confirmed COVID-19 by RT-PCR in Egypt, February–July 2020. Data were obtained from Egypt National Surveillance, bivariate and multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This previous systematic review and meta-analysis [ 37 ] also showed that pregnant women with COVID-19 are less likely to have those symptoms than non-pregnant women of reproductive age with COVID-19. The lower incidence of fever in our study may be related to the different definitions and measurements of fever between the included studies; for example, BahaaEldin's study [ 26 ] only provided data for body temperature > 38 °C, which this study directly adopted as the data for fever.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…This previous systematic review and meta-analysis [ 37 ] also showed that pregnant women with COVID-19 are less likely to have those symptoms than non-pregnant women of reproductive age with COVID-19. The lower incidence of fever in our study may be related to the different definitions and measurements of fever between the included studies; for example, BahaaEldin's study [ 26 ] only provided data for body temperature > 38 °C, which this study directly adopted as the data for fever.…”
Section: Discussionmentioning
confidence: 93%
“…We included 8 published studies [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ] with 859,278 COVID-19 female patients, of which 37,578 (4.37%) cases were pregnant patients. Most study designs are cohort studies or case-control studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations